Effects of Different Vegetable Oils and Animal Fat on Performance of Broiler Chicks - AL-Jaf, Barzan Fadhl Farıq; Kara, Muhammet Ali; Saeed, Rozhgar B. (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was carried out to find out effects of different vegetable oil and animal fat on broiler chick’s performance. The aim of this research was to identify the effects of different sources of oils on productive performance of broiler chicks. The experimental period was from 8th March 2017 to 27th April 2017. An overall of two hundred sixty, day-old of Ross 308 broiler chicks were distributed randomly on five treatments (4 replicates each with (13 chicks/ replicate). The treatments include T1: Control (without oil and fat addition); T2: Adding canola oil (%4); T3: Adding corn oil (%4); T4: Adding animal fat (%4); T5: Adding sunflower oil (%4). During the period of study, three types of diets were applied: Starter diet (from one to 20 day of the study), grower diet (from 21 to 42 days of study) and finisher diet (from 43 to 49 days of the study). Results indicated that supplementation of diets with different types of oil and animal fat significantly (p<0.05) improved live body weight and weight gain and feed conversation ratioratio and feed intake and production index, at periods (1-49) day. However, the effect of different vegetable oil and animal fat had no significant effect on abdominal fat and dressing percentage at period (1-49) day.
Keywords: Vegetable oil; animal fat; productive performance; broiler chicks